2017
DOI: 10.1021/acs.inorgchem.6b02822
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-Stabilized Superconductive Ionic Tantalum Hydrides

Abstract: High-pressure structures of tantalum hydrides were investigated over a wide pressure range of 0-300 GPa by utilizing evolutionary structure searches. TaH and TaH were found to be thermodynamically stable over this entire pressure range, whereas TaH, TaH, and TaH become thermodynamically stable at pressures greater than 50 GPa. The dense Pnma (TaH), R3̅m (TaH), and Fdd2 (TaH) compounds possess metallic character with a strong ionic feature. For the highly hydrogen-rich phase of Fdd2 (TaH), a calculation of elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 76 publications
2
26
2
Order By: Relevance
“…A review of the experimental studies, coupled with the results of DFT calculations that investigated the structures and electronic structures of the hydrides of tantalum up to 300 GPa is given in Ref. 124 This study showed that the XRD patterns for the theoretically predicted ambient pressure phases of Ta 2 H (C222) and Ta 5 H (C2), shown in Fig. 5(b,c), agreed well with those determined experimentally.…”
Section: Group 5: Vanadium Niobium Tantalumsupporting
confidence: 65%
“…A review of the experimental studies, coupled with the results of DFT calculations that investigated the structures and electronic structures of the hydrides of tantalum up to 300 GPa is given in Ref. 124 This study showed that the XRD patterns for the theoretically predicted ambient pressure phases of Ta 2 H (C222) and Ta 5 H (C2), shown in Fig. 5(b,c), agreed well with those determined experimentally.…”
Section: Group 5: Vanadium Niobium Tantalumsupporting
confidence: 65%
“…The following works refer to studies of binary hydrides under pressure for which some of the information was taken Fig. 21: Li [542], K [543], Fr [434], Be [544], Mg [545], Ca [176], Sr [546,547] Ba [548], Ra [434], Sc [549], Y [182], La [182,177], (Ce, Pr, Nd, Ho, Er, Tm, and Lu) [434], Ac [550], Th [551], Pa [434,552], U [553], (Np, Cm) [434], (Ti,Zr,Hf) [434], V [554], Nb [555,556], Ta [557], Cr [558], W [559], Tc [560], Ru [561], Os [562], (Rh,Ir) [563], Pd [440,564], Pt [565,566,563,567], Au [563], B [568], Al [569], Ga [570], In [571], Si [159,572], Ge [573,574,…”
Section: Appendixmentioning
confidence: 99%
“…10 After the maximum a sharp decline of maxT C occurs down to 13 K for Hf-H system (HfH 2 ) at 260 GPa, 12 while for the tantalum hydride Fdd2-TaH 6 was predicted as a superconductor with T C = 136 K at 300 GPa. 29 Hafnium has [Xe]4f 14 5d 2 6s 2 electronic configuration with two d-electrons where the only deep lying fully filled f-shell may negatively influent the superconducting properties of Hf-H phases. Obtained "failure" in the maxT C (N d ) dependence at the N d = 4 indicates about the presence of new stable polyhydrides in Hf-H system with higher T C .…”
Section: Period 6 Cs-ba-la-hf-tamentioning
confidence: 99%